2008
DOI: 10.1038/bjp.2008.152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a CNS penetrant, selective M1muscarinic receptor agonist, 77‐LH‐28‐1

Abstract: Background and purpose: M 1 muscarinic ACh receptors (mAChRs) represent an attractive drug target for the treatment of cognitive deficits associated with diseases such as Alzheimer's disease and schizophrenia. However, the discovery of subtypeselective mAChR agonists has been hampered by the high degree of conservation of the orthosteric ACh-binding site among mAChR subtypes. The advent of functional screening assays has enabled the identification of agonists such as AC-42 (4-nbutyl-1-[4-(2-methylphenyl)-4-oxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
138
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(150 citation statements)
references
References 39 publications
12
138
0
Order By: Relevance
“…The apparent binding affinity (pK B ) for each agonist is summarized in Table 1. Consistent with previous reports, both AC-42 and 77-LH-28-1 are able to displace specific [ 3 H]NMS binding from M 2 and M 3 mACh receptors (Spalding et al, 2002;May et al, 2007;Langmead et al, 2008a) with 77-LH-28-1 and AC-42 apparent affinities at the M 2 subtype being comparable with those observed at the M 1 mACh receptor (Table 1).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The apparent binding affinity (pK B ) for each agonist is summarized in Table 1. Consistent with previous reports, both AC-42 and 77-LH-28-1 are able to displace specific [ 3 H]NMS binding from M 2 and M 3 mACh receptors (Spalding et al, 2002;May et al, 2007;Langmead et al, 2008a) with 77-LH-28-1 and AC-42 apparent affinities at the M 2 subtype being comparable with those observed at the M 1 mACh receptor (Table 1).…”
supporting
confidence: 91%
“…Recent studies have reported actions of AC-42 and 77-LH-28-1 at non-M 1 mACh receptor subtypes (May et al, 2007;Langmead et al, 2008a). Here, we have shown that both allosteric agonists can displace specific [ 3 H]NMS binding to the M 2 and M 3 mACh receptors (Table 1).…”
Section: Determination Of Agonistsupporting
confidence: 59%
See 1 more Smart Citation
“…117 77-LH-28-1 (34, Figure 23), an M 1 mAChR-selective compound closely structurally related to the AC compounds, demonstrated agonistic behavior at rat hippocampal M 1 mAChRs in vitro and CNS penetration leading to the stimulation of rat hippocampal cell firing in vivo. 124 Furthermore, activation of M1 mAChRs by 77-LH-28-1 enhanced NMDA receptor activation in vitro, facilitating long-term potentiation. 125 Consistent with the interactions of AC-42, the mAChR orthosteric antagonists pirenzepine and scopolamine both produced a dextral displacement of the 77-LH-28-1 CRC; 124 however, 77-LH-28-1 has also been shown to compete with the prototypical muscarinic negative allosteric modulator C 7 /3-phth (at the NMS-occupied receptor), 115 adding weight to the theory that this scaffold interacts with portions of both orthosteric and allosteric sites on the M 1 mAChR.…”
Section: ■ M 1 Machr-selective Ligandsmentioning
confidence: 98%
“…TBPB promotes the processing of APP towards the non-amyloidogenic pathway, decreases Aβ production in vitro, and has been shown to improve cognition in animal models (122). 77-LH-28-1 is another potent, selective and CNS penetrant allosteric M1 agonist which was a structural analog of AC-42 that was reported to improve cognition in animal models (123) as did AC-260584 (124). However, it is unclear if any of these agents are being pursued for clinical development.…”
Section: Neurotransmitter-based Therapies Muscarinic Agonistsmentioning
confidence: 99%